A Review of the application of lifecycle analysis to renewable energy systems - Lund, C.; Biswas, Wahidul (Sage Publications, 2008)
The lifecycle concept is a "cradle to grave" approach to thinking about products, processes, and services, recognizing that all stages have environmental and economic impacts. Any rigorous and meaningful comparison of energy supply options must be done using a lifecycle analysis approach. It has been applied to an increasing number of conventional and renewable energy generation systems and in an increasing range of countries. There is now a good amount of research reporting the lifecycle environmental and economic aspects of power generation systems. This article reviews the existing lifecycle analyses of renewable energy systems to determine the current understanding of their full lifecycle impacts. These are then compared with each other and those of conventional power generation systems. The renewable energy systems reviewed include wind, solar photovoltaic, solar thermal (for electricity), hydroelectric, solid biomass, wave, geothermal, biogas, and tidal. The article also highlights the areas where more lifecycle analysis is needed.